Francis Alÿs : blueOrange 2004 : Kunstpreis des Deutschen Volksbanken und Raiffeisenbanken = Art Prize of the German Cooperative Banks. - Alÿs, Francis; Beck, Hubert; Biesenbach, Klaus; Pleister, Christopher; Sabau, Luminita; Exhibition. Francis Alÿs : blueOrange 2004. Martin-Gropius-Bau Berlin. 2004-09-02. 2004-10-18 (Berlin Köln : Martin-Gropius-Bau Berlin Verlag der Buchhandlung Walther König Köln, 2004)
In the contzext of blueOrange 2004, Alÿs has realized his first major installation in the inside courtyard of the Martin Gropius Building in Berlin. The audio/large-screen projection The Rehearsal 1 forms the heart of this multipartite piece, which draws on a variety of art genres. The present publication is appearing on the occasion of Francis Alÿs winning the inaugural blueOrange art prize. The book provides information on the art prize, the organizers, the goals and the competition procedure. And in addition to its function as an exhibition catalog, it also offers a range of essays designed to give the reader an in-depth introduction to Francis Alÿs' artistic world by shedding light on the oeuvre of this "flâneur" and global player from various different vantage points.
blueOrange, the new art prize launched by the German Cooperative Banks, has been awarded for the first time. Germany's best-paying prize for visual art is truly a prize that sets standards. The artist who has won the inaugural prize is Francis Alÿs, a cosmopolitan and one of the most interesting players in the current art scene. Born in Belgium, Alÿs has now lived in Mexico City for over 15 years, where he first made a name for himself with his "walks".
biog., ind. tent., gr. tent. p. 80-81
prijzen, bibliog. p. 81
Duits
Engels
boek
Keywords: Alys, Francis